The Relationship Between Smoking Habits and CO Levels of Adolescents in Middle Schools in Cinere District, Depok City, West Java, 2023 - Silmy Kaaffah; Raden Putri Annisya Affriany Praasetyo (Universitas Airlangga, 2024)
Background: Smoking is one of the highest risk factors for non-communicable diseases. Cigarettes Contain various dangerous substances, one of which is Carbon Monoxide (CO) which can cause multiple diseases of the lungs, heart, and other organs. The number of adolescent smokers has increased from 2014 to 2019. Riskesdas data in 2018 also shows that smokers start smoking at the age of 15-19 years. Aims: This study examines the relationship between smoking habits in adolescents aged 12-19 years in 16 secondary schools in the Cinere District, Depok City, West Java. Method: This is a cross-sectional study of 486 samples using a random sampling method. Data on smoking habits were analyzed descriptively and its relationship with CO levels was analyzed using the Kruskal-Wall Test. Result: Studies show that 51.9% of teenagers have never smoked, 18.6% of teenagers have tried smoking, 14.9% of teenagers smoke occasionally and 14.7% of teenagers smoke every day. 69.81% of teenage smokers smoke using conventional cigarettes, 14.1% use electronic cigarettes, and 16.1% use both. The average number of cigarettes smoked was 19 cigarettes per week. The average teenage smoker starts smoking at the age of 13 years and has been smoking for 31 months. The reason teenagers smoke is because of curiosity at 50.8% and being invited by friends at 46.6%. The presence of family members at home who smoke reaches 71.9% and there is a significant relationship between the presence of family members at home smoking and smoking habits among students. The Kruskal-Wall Test between smoking habits and CO levels produces a P-value of 0.001. Conclusion: It can be concluded that there is a significant relationship between smoking habits and CO levels in teenagers in secondary schools in the Cinere District area in 2023.